The Role of 360-Degree Performance Evaluation as a Performance Management Tool in Enhancing Student SatisfactIon: An Empirical Study within a University Organization - Ouahchi, Afaf (Journal of Ecohumanism, 2025)
This study investigates the impact of 360-degree performance evaluation as a performance management tool on student satisfaction in a university context. The research addresses a gap in performance management literature within higher education by examining whether comprehensive, multi-source feedback systems can enhance students’ educational experience. Methodology: A descriptive-analytical survey design was employed, targeting students of Management Sciences at the University of Algiers 3. Data were collected via a structured questionnaire (n ≈ 150) assessing perceptions of current performance evaluation practices and levels of student satisfaction. Reliability and validity checks (includeing expert review and Cronbach’s alpha >0.8) ensured a robust Instrument. Statistical analysis included descriptive metrics and correlation tests to evaluate the relationship between comprehensive performance evaluations and student satisfaction. Findings: Results indicate that performance evaluation practices in the university are of moderate effectiveness, while overall student satisfaction with the educational experience is relatively high. Importantly, a significant positive correlation was found between the extent of 360-degree evaluation practices and student satisfaction (Pearson r ≈ 0.34, p < 0.001). Perceived fairness and transparency In the evaluation process emerged as key factors influencing satisfaction. Implications: The findings suggest that implementing 360-degree feedback mechanisms can strengthen performance management in universities by providing actionable insights that improve teaching quality and services, thereby enhancing student satisfaction. The study contributes to higher education management literature and offers practical recommendations for university administrators seeking to improve student-centric outcomes through comprehensive performance evaluations. Originality: This research provides empirical evidence from a North AfrIcan university setting, extending performance management theory into the higher education domain and highlighting the role of fair, multi-perspective evaluations in promoting student satisfaction.